RANCANG BANGUN SISTEM MANAJEMEN LAYANAN BENGKEL RAHMAT97 AUDIO PROJECT BERBASIS WEB - Agung, Tri Cahya; Khairul, Khairul; Hendrawan, Jodi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Rahmad97 Audio is a car audio workshop that offers installation and sales services for audio systems. To improve service management and operational efficiency, a computerized web-based information system is needed. This study aims to design and develop a web-based service management system that facilitates the management of customer data, product inventory, transactions, and reports in an integrated manner. The system development follows the Waterfall model, consisting of requirements analysis, design, implementation, and testing stages.The implementation results show that the system significantly streamlines service and transaction recording processes, reduces manual entry errors, and enables real-time monitoring of workshop activities. The system includes multi-role login (admin, owner, and sales) to ensure data security and access control based on user roles. This web-based system helps the workshop manage its services more efficiently, in a structured and organized way, making it easier for business owners to monitor operations.Keywords: Information System, Car Audio Workshop, Service Management, Web-Based, PHP, MySQL Abstrak: Bengkel Rahmad97 Audio merupakan usaha jasa pemasangan dan penjualan perangkat audio mobil yang membutuhkan sistem informasi terkomputerisasi untuk mengelola layanan secara efektif. Penelitian ini bertujuan untuk merancang dan membangun sistem manajemen layanan bengkel berbasis web yang dapat membantu dalam pengelolaan data pelanggan, produk, transaksi, serta pelaporan secara terintegrasi. Metode pengembangan sistem yang digunakan adalah model Waterfall, yang meliputi tahapan analisis kebutuhan, perancangan, implementasi, dan pengujian. Hasil dari implementasi menunjukkan bahwa sistem ini mampu mempercepat proses pencatatan layanan dan transaksi, meminimalkan kesalahan pencatatan manual, serta memberikan kemudahan dalam monitoring aktivitas bengkel secara real-time. Sistem juga dilengkapi dengan fitur login multi-role (admin, owner, dan sales) untuk menjaga keamanan dan pembatasan akses data sesuai peran. Dengan adanya sistem ini, pengelolaan layanan bengkel menjadi lebih efisien, terstruktur, dan mudah diawasi oleh pemilik usaha.Kata kunci: Sistem Informasi, Bengkel Audio Mobil, Manajemen Layanan, Web, PHP, MySQL